Protein folding - Shakhnovich, Eugene (Henry Stewart Talks, 2007)
Introduction to principles of protein structure, The basic facts about protein folding, Cooperativity of protein structure formation, Necessary and sufficient conditions for protein sequences to fold, Concept of energy gap, Protein folding kinetics, Intermediates and transition state ensembles, Allatom folding simulations, Understanding protein folding pathways at atomic detail